24-h urinary sodium excretion and the risk of adverse outcomes. (16th November 2020) - Vuori, Matti A.; Harald, Kennet; Jula, Antti; Valsta, Liisa; Laatikainen, Tiina; Salomaa, Veikko; Tuomilehto, Jaakko; Jousilahti, Pekka; Niiranen, Teemu J.
Abstract: Aims: The objective was to evaluate whether sodium intake, assessed with the gold standard 24-h urinary collections, was related to long-term incidence of death, cardiovascular disease (CVD) and diabetes mellitus (DM). Methods: A cohort of 4630 individuals aged 25–64 years collected 24-h urine samples in 1979–2002 and were followed up to 14 years for the incidence of any CVD, coronary heart disease (CHD), stroke, heart failure (HF) and DM event, and death. Cox proportional hazards models were used to estimate the association between the baseline salt intake and incident events and adjusted for baseline age, body mass index, serum cholesterol, prevalent DM, and stratified by sex and cohort baseline year. Results: During the follow-up, we observed 423 deaths, 424 CVD events (288 CHD events, 142 strokes, 139 HF events) and 161 DM events. Compared with the highest quartile of salt intake, persons in the lowest quartile had a lower incidence of CVD (hazard ratio [HR] 0.70; 95% confidence interval [CI], 0.51–0.95, p  = .02), CHD (HR 0.63 [95% CI 0.42–0.94], p  = .02) and DM (HR 0.52 [95% CI 0.31–0.87], p  = .01). The results were non-significant for mortality, HF, and stroke. Conclusion: High sodium intake is associated with an increased incidence of CVD and DM.